Interactive Arabic E-Learning for Prospective Students Studying in the Middle East - Mohammad Zaelani Musonif; Hanik Mahliatussikah; Kholisin Kholisin (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
This research aimed to investigate the indicators in the analysis of needs for the development of Arabic language e-learning. The research was important as it served as the foundation for aspects that would be developed in the subsequent Research and Development phases. The research employed a descriptive research method with a quantitative approach. Data was collected through observation techniques, survey questionnaires, and literature review. The analysis results were aimed at determining the percentage values of each indicator and categorizing them based on these percentages. The findings of the needs analysis research indicated that there were six aspects that needed to be developed in the Markaz Arabiyah e-learning, namely usage guidelines for E-learning, self-learning materials, practice exercises, university selection exam simulations, information about universities in the Middle East, and discussion access.